Pengaruh Kompetensi Dan Kualitas Kerja Terhadap Prestasi Kerja Pegawai Pada Madrasah Tsanawiah Ponpes Al Muthmainnah Soromandi Kabupaten Bima - Ulma Susfiati; Jaenab Jaenab (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This study aims to determine the effect of competence and quality of work partially and simultaneously on employee performance at Madrasah Tsanawiah Islamic Boarding School Al Muthmainnah Soromandi, Bima Regency. The research methodology is associative. The population in this study included all employees at Madrasah Tsanawiah Islamic Boarding School Al Muthmainnah Soromandi, Bima Regency, totaling 32 people. The sampling technique used is saturated sampling. Data collection techniques by conducting observations, interviews, questionnaires, documentation and literature study. Data analysis techniques used are validity test, reliability test, classic assumption test, multiple linear regression, correlation coefficient, coefficient of determination, t test, and f test. The results of the t test show that the competency and work quality variables do not partially affect the work performance of employees at Madrasah Tsanawiah Islamic Boarding School Al-Muthmainnah Soromandi, Bima Regency. The results of the F test show that competency and work quality simultaneously affect employee performance at Madrasah Tsanawiah Islamic Boarding School Al-Muthmainnah Soromandi, Bima Regency.